2010
DOI: 10.1097/jom.0b013e3181c95b9e
|View full text |Cite
|
Sign up to set email alerts
|

Do Fear-Avoidance Beliefs Play a Role on the Association Between Low Back Pain and Sickness Absence? A Prospective Cohort Study Among Female Health Care Workers

Abstract: Health care workers have a high prevalence of sickness absence because of low back pain (LBP). This study examined whether fear-avoidance beliefs (FAB): 1) predicted sickness absence and 2) moderated the association between LBP and sickness absence among 1724 newly educated health care workers with LBP >or= day during the previous 12 months. High FAB was associated with sickness absence days 1 year later (relative risk, 1.45, 95% confidence interval = 1.24 to 1.70), controlled for LBP, previous sickness absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 41 publications
3
56
0
1
Order By: Relevance
“…17,20,29,45,49,53,57 Recently, it has been suggested that pain-related fear should be considered within a motivational context. More specifically, the experience of pain might not only lead to the development of pain-related fear, but may also activate the goal to control or avoid (further) harm.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,29,45,49,53,57 Recently, it has been suggested that pain-related fear should be considered within a motivational context. More specifically, the experience of pain might not only lead to the development of pain-related fear, but may also activate the goal to control or avoid (further) harm.…”
Section: Introductionmentioning
confidence: 99%
“…For low back pain patients, painrelated fear is a risk factor for the development of chronic low back pain through diminished participation in activities of daily life, for greater perceived disability, greater work loss, and more frequent sick leave as well as for poorer treatment performance 14,34 . Several prospective studies suggest that fear-avoidance beliefs may influence the transition from acute to chronic low back pain and associated outcomes, such as disability and sick leave 35,36 .…”
Section: Current State Of Evidencementioning
confidence: 99%
“…As well as being an independent risk factor for cardiovascular disease (Stansfeld et al 2002, van Amelsvoort et al 2003, it is also very costly with respect to work absenteeism ( Hemingway el al. 1997, Borritz et al 2010, Jensen et al 2010. Over the previous 30 years, high work demands, low decision latitude, and low levels of social support at work, have been identified as important constructs in relation to work related psychological well-being (Karasek, 1979;Johnson and Hall, 1988, van der Doef et al 1999, de Lange et al 2003, Hausser et al 2010.…”
Section: Introductionmentioning
confidence: 99%